Artificial Intelligence Driven Accounting: Benefits, Risks, And The Road Ahead - Kale Nilesh (ITM Web of Conferences)
The digital revolution has peaked with AI infusion in the workspace. This has caused immense convenience to the people who use AI tools for their everyday tasks. The same has potential risks associated with AI’s existence. This study explores the use of AI in accounting, auditing and finance sector and how it could impact the accounting procedures and financial operations. This is an exploratory study based on secondary data collected to give analytical evidence to the theoretical ideas proposed. This study proposes to answers the questions like can we use AI to detect accounting frauds? Will it raise complications? The study also proposes AI Deception Cycle (AI-DC) where AI enters into a puzzle created by itself and fails to work on it. This study aims at identifying major challenges and offer theoretical ways that accounting and finance experts can practice in order to mitigate risks as they exploit the use of AI effectively in their operations.